Differentiated Instruction to Enhance Critical Thinking Character in Islamic Elementary School Students in Makassar - Irmawati Thahir; Muhammad Nawir; Nurasia Natsir (International Journal of Studies in International Education, 2025)
This research aims to analyse the effectiveness of differentiated instruction implementation in enhancing critical thinking character in Islamic Elementary School students in Makassar. The research employed a mixed-method approach with an embedded experimental design. The research sample consisted of 68 fourth and fifth-grade students from three Islamic Elementary Schools in Makassar, selected through purposive sampling. Data were collected through observation, critical thinking ability tests, interviews, and documentation. Differentiated instruction was implemented for 12 weeks, considering variations in students' learning readiness, interests, and learning profiles. The results showed that: (1) the implementation of differentiated instruction was effective with an implementation rate of 87.5%; (2) there was a significant improvement in students' critical thinking abilities with an effect size of 0.82 (high category); (3) the three aspects of critical thinking that experienced the highest improvement were analyzing arguments, evaluating information, and drawing conclusions based on evidence; (4) success supporting factors included comprehensive lesson planning, school leadership support, teacher competence, and integration of Islamic values in the learning process. This research recommends the implementation of differentiated instruction as a strategy to develop students' critical thinking abilities while considering individual learning characteristics and needs.